The diffusion of information technology in Europe - Harald Gruber (EIB Papers, 2001)
Europe, as all modern economies, is shifting towards an information-based society, where Information Technology (IT) is dramatically modifying patterns of production and consumption and the modern way of life. Low-cost data processing and transmission technologies are leading the way not only in a technological revolution, but also in an economic and social revolution. The main drivers for these trends are technology and market liberalisation. Technological advances, in particular in microelectronics and optical fibres, have drastically reduced the cost of data processing and transmission. In parallel, reduction of trade barriers for IT equipment and the market liberalisation in key sectors adopting IT, such as telecommunications, mobilised huge amounts of private funding for the adoption of new products and services.
Keywords: 330; Informationstechnik; Telekommunikation; Mobiltelefon; Innovationsdiffusion; EU-Staaten